YUQORI QON BOSIMIGA EGA BO‘LGAN SHAXSLARNING INTELLEKTUAL TAHLILINI AMALGA OSHIRISH - Eshboyev, E.A.; Klicheva, F.G.; Valiyeva, Sh.T. (SCIENCE and SOCIETY, 2022)
The article presents an algorithm of a software tool for predicting high blood pressure in clients using artificial intelligence methods, scaling of data collected as a result of observations, their visualization, presentation of forecast results in numerical and graphical form.